2018
DOI: 10.1177/0030222818754668
|View full text |Cite
|
Sign up to set email alerts
|

“We Take Care of People; What Happens to Us Afterwards?”: Home Health Aides and Bereavement Care in Hospice

Abstract: After a hospice patient dies, hospice providers can experience a variety of emotional responses. While work has been done on social workers' and nurses' reactions to patient death, home health aides (HHAs) have been overlooked. To address this gap, we conducted focus groups and individual qualitative interviews with 14 hospice HHAs. Questions covered HHAs' grief responses and how they coped with grief. We found a high burden of grief reactions; many HHAs often developed very close patient relationships. HHAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The participants identified a variety of ways their relationships with their patients and the specific functions of their job informed their experience of loss. Consistent with previous research of home health workers (Ghesquiere & Bagaajav, 2020;, DCWs incorporate their personal understandings of both caring for others and how to grieve, including though personal mantras and spirituality. Both personal coping strategies and their understanding of loss contributed to how they managed anticipatory grief and the impact of losing a patient through death or relocation.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The participants identified a variety of ways their relationships with their patients and the specific functions of their job informed their experience of loss. Consistent with previous research of home health workers (Ghesquiere & Bagaajav, 2020;, DCWs incorporate their personal understandings of both caring for others and how to grieve, including though personal mantras and spirituality. Both personal coping strategies and their understanding of loss contributed to how they managed anticipatory grief and the impact of losing a patient through death or relocation.…”
Section: Discussionmentioning
confidence: 72%
“…Results show the perceived connection and relationship influence the experience of care transition and agencies have an opportunity to develop space for DCWs to grieve their losses. Currently, DCWs do not have adequate time between losing one patient and caring for another (Ghesquiere & Bagaajav, 2020; Tsui et al, 2019). To better support DCWs, agencies could provide an outlet such as an answering service (Kusmaul & Wladkowski, 2021), or group opportunities (Ghesquiere & Bagaajav, 2020) to provide an opportunity to share their grief during their paid work hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited qualitative studies exploring the experiences of home carers following the death of a patient. One study of home health aides in a New York City hospice setting reported emotional and grief responses, with coping through acceptance, meaning-making, and social support (Ghesquiere & Bagaajav, 2020). In another study, home health aides working in New York City reported stressors surrounding the immediate loss of income and financial security; coping included self-reliance, faith and prayer, social support, and education (Franzosa et al, 2019).…”
mentioning
confidence: 99%